2006
DOI: 10.1021/ja060087+
|View full text |Cite
|
Sign up to set email alerts
|

Li+-Catalyzed Radical Polymerization of Simple Terminal Alkenes

Abstract: Solutions of Li+ salts of highly alkylated derivatives of the monocarbadodecaborate anion in 1,2-dichloroethane catalyze the radical polymerization of simple terminal alkenes, dienes, and alkynes under ambient conditions, initiated by azoisobutyronitrile, di-tert-butyl peroxide, or atmospheric air.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
78
1

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 71 publications
(86 citation statements)
references
References 28 publications
7
78
1
Order By: Relevance
“…However, for a ring-closure-type radical clock, we [19] were able to show that complexation of the double bond of the intermediate hex-1-en-6-yl radical [20] to a lithium cation decreases the calculated activation barrier for the ring-closing rearrangement significantly. This effect is supported indirectly by recent work of Michl and co-workers, [21,22] who showed that "naked" lithium cations have a catalyzing effect on the radical polymerization of terminal olefins, in accord with a proposal made 20 years ago on the basis of ab initio calculations [23] and a recent more-detailed study at higher theoretical levels. [24] However, all these observations pertain to radicals that contain a double bond, which can complex the lithium cation moderately well.…”
Section: Introductionsupporting
confidence: 56%
“…However, for a ring-closure-type radical clock, we [19] were able to show that complexation of the double bond of the intermediate hex-1-en-6-yl radical [20] to a lithium cation decreases the calculated activation barrier for the ring-closing rearrangement significantly. This effect is supported indirectly by recent work of Michl and co-workers, [21,22] who showed that "naked" lithium cations have a catalyzing effect on the radical polymerization of terminal olefins, in accord with a proposal made 20 years ago on the basis of ab initio calculations [23] and a recent more-detailed study at higher theoretical levels. [24] However, all these observations pertain to radicals that contain a double bond, which can complex the lithium cation moderately well.…”
Section: Introductionsupporting
confidence: 56%
“…LiCl induced heterotactic specificity in CF 3 CH 2 OH, which was the same as LiNTf 2 . 59 The addition of an equimolar amount of NaNTf 2 or KNTf 2 also enhanced the polymer yields and molecular weights when the DMAAm polymerization reaction was conducted in polar solvents, except for KNTf 2 in CF 3 CH 2 OH (Table 4, runs [30][31][32][33][34][35]. The r diad content reached up to 65% in THF, which is comparable to the highest r diad content of 69% reported to date for radically prepared poly (DMAAm)s. 58 On the other hand, LiOTf exhibited a different effect to that of LiNTf 2 and LiCl, in that it gave syndiotactic-Scheme 2 Relationship between the stoichiometry of the DMAAm-Li + complex and the stereospecificity of the DMAAm polymerization.…”
Section: Relationship Between Complex Structure and Stereospecificitymentioning
confidence: 55%
“…After a day on the benchtop, these microcrystalline powders spontaneously turn into an oligomeric gummy material whose NMR no longer shows any vinylic protons. 15 This transformation does not occur in the absence of air, and it was ultimately proposed that oxygen acts as a radical initiator, 16 likely by oxidizing the carborate anion to a radical, which in turn initiates polymerization. Our group has since used oxygen to initiate other alkene radical polymerizations in the presence of LiCB 11 (CH 3 ) 12 under ambient conditions.…”
Section: Methodsmentioning
confidence: 99%